FIKIH PERNIKAHAN DALAM TAFSIR AḌWA’ AL-BAYĀN - Nashirudin, Muh. (Fakultas Syariah (Syari'ah Faculty ), 2015)
This writing describes the thought of Muhammad al-Amin ash-Shinqiṭi in his tafsir of Adhwa’ al-Bayan especially that is concerning mut’ah marriage, marrying women who committed adultery and women of the people of the book. The tafsir of Adhwa’ al-Bayan combines between textual method and contextual method, between tafsir bi al-ma’sur and tafsir bi ar-ra’y. However it has more tendencies in tafsir bi al-ma’tsur (understanding and interpreting the verses of al-Qur’an by making connections between the verses each other, between hadits, atsar of sahabah, and linguistic analysis. After describing Muhammad al-Amin ash-Shinqiṭi’s thought on Islamic family law and comparing it with the thoughts of other Islamic scholars, his thought then can be understood. According to him, mut’ah marriage is against the main purpose of marriage. Next, he tries to combine between two opinions by validating the two interpretations of nikah in one verse. Further he categorizes ahl al-Kitab into musyrik. His thought of Islamic law is based on the construct of tafsir method which he uses as a consistency in implementing the tafsir method and the paradigm of Islamic law. For these three problems, ash-Shinqiṭi tends to follow the opinion of majority of Islamic scholars about mut’ah marriage, marrying women who committed adultery and women of the people of the book.